Implementing Gender Equity Policies in a University Sport Organization: Competing Discourses from Enthusiasm to Resistance. Issue 2 (3rd April 2017) - Soler, Susanna; Prat, Maria; Puig, Núria; Flintoff, Anne
ABSTRACT: Gender policies in sports have expanded considerably in most countries in recent decades. Nevertheless, the implementation of these policies in sports organizations is by no means an automatic process. This article explores what happens when gender equity policies are applied in an university sports organization. Participatory action research over a four-year period was developed by the authors to increase the participation of women, and it also aimed to explore the perceptions and thoughts of key actors regarding equity actions. The analysis shows the participation numbers in the specific promotional campaign and reveals a wide range of responses among staff, ranging from enthusiasm and interest to resistance and fear. Gender equity actions often encounter resistance which cannot, and should not, be ignored. This article highlights certain forms of resistance that proposals of this kind should be prepared for.